THE URGENCY OF HALAL CERTIFICATION IN ISLAMIC ECONOMIC PRODUCT TRANSACTIONS: PERSPECTIVE OF NATIONAL REGULATION AND ISLAMIC LAW - Cut Afrida Yulianti (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
safety, health, and product quality. This study aims to analyse the urgency of halal certification in sharia economic product transactions based on national regulations and Islamic legal perspectives. The method used is a normative study with a juridical and maqashid sharia approach. The findings indicate that halal certification is not only a moral obligation but also a legal-formal requirement regulated under Law No. 33 of 2014 on Halal Product Assurance. From a Sharia perspective, halal certification is part of the effort to safeguard the welfare of the community (maslahah) and protect against what is haram (dar' al-mafasid). In conclusion, halal certification plays a crucial role in ensuring public trust in the Islamic economic system and supporting the growth of the national halal industry